A Late Silurian (Pridolian) age for the Eastport Formation, Maine:: a review of the fossil, stratigraphic, and radiometric-age data - Churchill-Dickson, Lisa (Atlantic Geology, 2004)
ABSTRACT The Eastport Formation is part of a larger volcaniclastic sequence (the Coastal Volcanic Belt) that extends from Massachusetts, USA, into New Brunswick, Canada. It represents a portion of Avalonia that was accreted to Laurentia during the Acadian orogeny. For more than thirty years the age of this formation has been regarded as Early Devonian (Lochkovian or Pragian) based on a new and yet undescribed ostracode genus. However, careful analysis of the fossil data indicates a Late Silurian (Pridolian) age for the fauna, and shows that the evidence used to assign a Devonian age should have been regarded as provisional. This interpretation is additionally strengthened by local stratigraphy and recent radiometric dating, both of which support a Late Silurian age for the Eastport Formation.